Neuroprotective potency of mangiferin against 3-nitropropionic acid induced Huntington’s disease-like symptoms in rats: possible antioxidant and anti-inflammatory mechanisms - Lum, Pei Teng; Sekar, Mahendran; Seow, Lay Jing; Shaikh, Mohd Farooq; Arulsamy, Alina; Retinasamy, Thaarvena; Gan, Siew Hua; Gnanaraj, Charles; Mohd Esa, Norhaizan; Ramachawolran, Gobinath; Subramaniyan, Vetriselvan; Chinni, Suresh V.; et al. (Frontiers Media, 2023)
Huntington’s disease (HD), a neurodegenerative disease, normally starts in the prime of adult life, followed by a gradual occurrence of psychiatric disturbances, cognitive and motor dysfunction. The daily performances and life quality of HD patients have been severely interfered by these clinical signs and symptoms until the last stage of neuronal cell death. To the best of our knowledge, no treatment is available to completely mitigate the progression of HD. Mangiferin, a naturally occurring potent glucoxilxanthone, is mainly isolated from the Mangifera indica plant. Considerable studies have confirmed the medicinal benefits of mangiferin against memory and cognitive impairment in neurodegenerative experimental models such as Alzheimer’s and Parkinson’s diseases. Therefore, this study aims to evaluate the neuroprotective effect of mangiferin against 3-nitropropionic acid (3-NP) induced HD in rat models. Adult Wistar rats (n = 32) were randomly allocated equally into four groups of eight rats each: normal control (Group I), disease control (Group II) and two treatment groups (Group III and Group IV). Treatment with mangiferin (10 and 20 mg/kg, p. o.) was given for 14 days, whereas 3-NP (15 mg/kg, i. p.) was given for 7 days to induce HD-like symptoms in rats. Rats were assessed for cognitive functions and motor coordination using open field test (OFT), novel object recognition (NOR) test, neurological assessment, rotarod and grip strength tests. Biochemical parameters such as oxidative stress markers and pro-inflammatory markers in brain hippocampus, striatum and cortex regions were evaluated. Histopathological study on brain tissue was also conducted using hematoxylin and eosin (H&E) staining. 3-NP triggered anxiety, decreased recognition memory, reduced locomotor activity, lower neurological scoring, declined rotarod performance and grip strength were alleviated by mangiferin treatment. Further, a significant depletion in brain malondialdehyde (MDA) level, an increase in reduced glutathione (GSH) level, succinate dehydrogenase (SDH), superoxide dismutase (SOD) and catalase (CAT) activities, and a decrease in tumor necrosis factor-alpha (TNF-α), interleukin-1 beta (IL-1β) and interleukin-6 (IL-6) levels were observed in mangiferin treated groups. Mangiferin also mitigated 3-NP induced histopathological alteration in the brain hippocampus, striatum and cortex sections. It could be inferred that mangiferin protects the brain against oxidative damage and neuroinflammation, notably via antioxidant and anti-inflammatory activities. Mangiferin, which has a good safety profile, may be an alternate treatment option for treating HD and other neurodegenerative disorders. The results of the current research of mangiferin will open up new avenues for the development of safe and effective therapeutic agents in diminishing HD.